The policy process in the modern state - Hill, Michael (London : Prentice-Hall, 1997)
Rev. ed of : The Policy process in the modern capitalist state/ Christopher Ham, Michael Hill --2nd ed. c1993
Keywords: Bureaucracy; Policy sciences